Ethnomathematics Exploration of Maggurecceng, Engklek, and Sayyang Pattudu in the Concept of Number - Naufal, Muhammad Ammar; Ja'faruddin, Ja'faruddin; Ihsan, Hisyam (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2024)
Ethnomathematics connects cultural practices with mathematical concepts, offering an engaging learning approach for students. This study conducts a Systematic Literature Review (SLR) of 178 articles from the Google Scholar database (2012 2022) to explore the relationship between traditional cultural activities and the concept of numbers. It focuses on cultural elements such as Maggurecceng, Engklek, and Sayyang Pattudu, revealing how these traditional games can enhance students’ understanding of number concepts, such as addition, multiplication, and numerical comparisons. The findings highlight the potential of ethnomathematics to foster mathematical abilities through culturally relevant learning activities, thereby promoting both mathematical comprehension and cultural appreciation in educational contexts. This review emphasizes the integration of culture into mathematics education as a tool for improving learning outcomes, particularly in developing numerical literacy.